الهجرة غير الشرعية بين المواثيق الدولية والقيم الإنسانية (Revue El-Wahat pour les Recherches et les Etudes, 2021)
Illegal Immigration Is A Manifestation Of Man's Constant Search For Decent Living, In Which Man Moves From Place To Place In Search Of The Desired HappinessIn This Context, International Legal Documents Guarantee The Illegal Immigration Of Migrants, Ranging From Fundamental Rights Which Should Not Be Suspended Or Suspended In Exceptional Circumstances, The Principle Of Relief And The Right To Return To The Country Of Origin.All These Guarantees And Others I Will Try To Shed Light In My Article, So As To Achieve Human Values In Dealing With Illegal Immigrants.   Keywords – Illegal Migration - International Conventions - Human Values